A new species of Protoplotina Miyatake (Coleoptera: Coccinellidae) from Tamil Nadu, India - Poorani, J.; Anuradha, C.; Thanigairaj, R. (Zootaxa, 2021)
Protoplotina ambigua sp. n. (Coccinellidae: Plotinini) from the southern Indian state of Tamil Nadu is described and illustrated. This is the third species of the genus reported from India. Immature stages of the genus Protoplotina are briefly described and illustrated for the first time with notes on host association. A revised key to the known species of the genus is also included.